Navigating Faith: Unveiling the Reliability and Validity of the Circumplex Religious Orientation Inventory (CROI) in Indonesia's Diverse Spiritual Landscape - Mira Sekar Arumi; Marina Sulastiana; Anissa Lestari Kadiyono; Retno Hanggarani Ninin (Islamic Guidance and Counseling Journal)
Despite Indonesia's designation as a religiously diverse nation, there is a notable absence of a universally applicable religiosity scale that encompasses all faiths within its borders. Thus, this paper aims to translate, validate, and ensure the reliability of the Circumplex Religious Orientation Inventory (CROI), originally developed by Krauss and Hood in 2013, within the Indonesian cultural context. Data were collected via an online survey administered to 571 male and female volunteers in Indonesia, aged 18 years and above. The translation and assessment of the scale's psychometric properties, including internal consistency, factor analysis, convergent validity, time consistency, and socio-demographic analysis, were conducted. The study findings revealed that the Indonesian version of the CROI exhibited strong internal consistency, positive factor analysis outcomes, consistent responses over time, socio-demographic variations, as well as robust convergent and discriminant validity when compared to widely recognized measures of religiosity, religious orientation, intellectual humility, and religious tolerance. In conclusion, this research underscores the Indonesian version of the CROI as a valuable instrument for assessing religious orientation among individuals aged 18 and above in Indonesia.